Audio-visual infography: from image to space - Ràfols Cabrisses, Rafael (Estudios sobre el Mensaje Periodístico, 2012)
The development of digital technology in the creation and manipulation of image has achieved such a level that doesn’t correspond to its current use in the construction of audio-visual news. A variety of circumstances can explain this situation and, among them, I would like to emphasize the fact that infography is only considerate as a mean to create images, when, under my point of view, it should be understood, above all, as a mean to construct spaces.
Keywords: animation graphics; infography; information design; audio-visual space.